Normal : one kid's extraordinary journey - Newman, Magdalena M.; Newman, Nathaniel; Liftin, Hilary (Houghton Mifflin Harcourt, 2020)
Nathaniel and his mother, Magda, tell the story of Nathaniel's life with Treacher Collins syndrome, from having sixty-seven surgeries before the age of fifteen to making friends, dealing with people's reactions to his appearance, and trying to have a normal childhood.